2014
DOI: 10.1371/journal.pcbi.1003547
|View full text |Cite
|
Sign up to set email alerts
|

A Synergism between Adaptive Effects and Evolvability Drives Whole Genome Duplication to Fixation

Abstract: Whole genome duplication has shaped eukaryotic evolutionary history and has been associated with drastic environmental change and species radiation. While the most common fate of WGD duplicates is a return to single copy, retained duplicates have been found enriched for highly interacting genes. This pattern has been explained by a neutral process of subfunctionalization and more recently, dosage balance selection. However, much about the relationship between environmental change, WGD and adaptation remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 61 publications
5
21
0
Order By: Relevance
“…Finally, we examined the relation between the level of protein connectivity and retention rates. The number of protein-protein interactions was previously taken as a proxy for sensitivity to dosage imbalance (Prachumwat and Li 2006;Flagel and Wendel 2009;Rodgers-Melnick et al 2013;Cuypers and Hogeweg 2014). We observed that mouse orthologs of zebrafish 3R ohnologs had a significantly higher connectivity than orthologs of singletons ( Figure S11A), in agreement with previous studies (Hakes et al 2007;Liang and Li 2007;Rodgers-Melnick et al 2012).…”
Section: The Nervous System Bias Is Independent From the Dosage-balansupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, we examined the relation between the level of protein connectivity and retention rates. The number of protein-protein interactions was previously taken as a proxy for sensitivity to dosage imbalance (Prachumwat and Li 2006;Flagel and Wendel 2009;Rodgers-Melnick et al 2013;Cuypers and Hogeweg 2014). We observed that mouse orthologs of zebrafish 3R ohnologs had a significantly higher connectivity than orthologs of singletons ( Figure S11A), in agreement with previous studies (Hakes et al 2007;Liang and Li 2007;Rodgers-Melnick et al 2012).…”
Section: The Nervous System Bias Is Independent From the Dosage-balansupporting
confidence: 90%
“…On the other hand, whole-genome duplications have often been claimed to be beneficial in the long term, since the addition of new genes to genomes provides new material for evolution to act on, and increases evolvability of the lineages (Cuypers and Hogeweg 2014;Kondrashov 2012;Van de Peer, et al 2009). A particularly interesting example is the ancestral 2R event, which added to the genomes of vertebrates a large number of regulatory genes, such as transcription factors, as an indirect effect of purifying selection for gene dosage balance.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the modular arrangement of duplicated GRNs may also result in functionally redundant modules, contributing to the genetic or mutational robustness at the GRN level. This facilitates the rewiring of novel functional modules without disturbing the ancestral one, a feature that is expected to be especially advantageous under unstable challenging environments (23,36). In this respect, our observations are compatible with previous claims that increased modularity results in increased evolvability (32,(39)(40)(41)(42)(43)(44).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly to what happens for BMP16, parallel lineagespecific gene losses have been reported for other genes that were present at the base of the vertebrate lineage and have been lost in selected taxa throughout evolution [44][45][46][47]. Gene retention is often associated with adaptive advantages [48,49] and the maintenance of BMP16 in Lepidousaria genomes is most likely due to a selective advantage related to specific traits (e.g. locomotion, reproduction, feeding, adaptation to a particular environment) that the gene confers (see below for our hypothesis of the adaptive advantage promoted by BMP16).…”
Section: Discussionmentioning
confidence: 73%